ANALISIS BEBAN KERJA IBU DAN PENGASUHAN ANAK USIA 3-5 TAHUN PADA KELUARGA MISKIN DI KECAMATAN BOGOR SELATAN - Daniar Yulianis; Drajat Martianto; Dwi Hastuti (Jurnal Ilmu Keluarga dan Konsumen, 2008)
The objective of study was to study mother work-load and its association with caring practice of 3-5 years old children in poor family at South Bogor Sub District. Cikaret, Empang, and, Bondongan area chosen as locations of the study. Ninety children within age of 3 to 5 years were selected purposively. Data collection was conducted from May to July 2003. Time allocation data were gathered using 24 hour recall method. Descriptive statistics and Rank-Spearman Correlation were applied to analyze data. Result showed that age of most parents were ranging from 26 to 35 years, most of them had low educational background, worked as manual labor, with average income/capita/month was Rp 86,400.00. Work-load and time of caring of most mothers were at moderate category, while caring practice was high. Most of mothers perceived they had light work-load, and those who had light work-load also perceived that they had light work-load. Caring practices of mothers were different according to their work-load. Working mothers spent 4.66 hours while non-working mothers spent 6.24 hours with their children. Results showed that mother’s work-load not necessarily associated with time spent for caring practice, and time spent for caring practice not necessarily increased quality of feeding practice.